Seven years of Non-invasive Follicular Thyroid Neoplasm with Papillary-like Nuclear Features (NIFTP): Rate of Acceptance and Variation of Diagnostic Approaches Across Different Continents - Williams, Michelle D; Liu, Zhiyan; Rossi, Esther Diana; Agarwal, Shipra; Ryška, Aleš; Ghuzlan, Abir Al; Bychkov, Andrey; Baloch, Zubair; Chernock, Rebecca; Chiosea, Simion L; Cipriani, Nicole A; Erkilic, Suna; et al. (The Journal of clinical endocrinology and metabolism, 2024)
CONTEXT: Noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) was introduced as a new entity replacing the diagnosis of noninvasive encapsulated follicular variant of papillary thyroid carcinoma (PTC). Significant variability in the incidence of NIFTP diagnosed in different world regions has been reported. OBJECTIVE: To investigate the rate of adoption of NIFTP, change in practice patterns, and uniformity in applying diagnostic criteria among pathologists practicing in different regions. METHODS: Two surveys distributed to pathologists of the International Endocrine Pathology Discussion Group with multiple-choice questions on NIFTP adoption into pathology practice and whole slide images of 5 tumors to collect information on nuclear score and diagnosis. Forty-eight endocrine pathologists, including 24 from North America, 8 from Europe, and 16 from Asia/Oceania completed the first survey and 38 the second survey. RESULTS: A 94% adoption rate of NIFTP by the pathologists was found. Yet, the frequency of rendering NIFTP diagnosis was significantly higher in North America than in other regions (P = .009). While the highest concordance was found in diagnosing lesions with mildly or well-developed PTC-like nuclei, there was significant variability in nuclear scoring and diagnosing NIFTP for tumors with moderate nuclear changes (nuclear score 2) (case 2, P < .05). Pathologists practicing in North America and Europe showed a tendency for lower thresholds for PTC-like nuclei and NIFTP than those practicing in Asia/Oceania. CONCLUSION: Despite a high adoption rate of NIFTP across geographic regions, NIFTP is diagnosed more often by pathologists in North America. Significant differences remain in diagnosing intermediate PTC-like nuclei and respectively NIFTP, with more conservative nuclear scoring in Asia/Oceania, which may explain the geographic differences in NIFTP incidence.
Keywords: lékařská praxe - způsoby provádění; Practice Patterns, Physicians'; Oceánie; Cell Nucleus; folikulární adenokarcinom; Asia; Europe; Thyroid Neoplasms; Asie; buněčné jádro; Oceania; Thyroid Cancer, Papillary; Adenocarcinoma, Follicular; Evropa; papilární karcinom; nádory štítné žlázy; lidé; Humans; Carcinoma, Papillary; North America; papilární karcinom štítné žlázy; Severní Amerika